Youth Generation Moral Crisis in Quran Perspective Cause Analysis and Solution - Mulyani, Sri; Setiawan, Budi (STKQ Al-Hikam Depok, 2025)
The moral crisis among the younger generation has become a serious challenge in modern society, especially amid the rapid currents of globalization, digital information, and swift cultural changes. Phenomena such as promiscuity, drug abuse, the erosion of moral values, and the rise of cybercrime indicate that many youths are losing direction in life and experiencing a crisis of spiritual identity. This study aims to analyze the main causes of the moral crisis and formulate solutions from the perspective of the Qur’an. Using a descriptive qualitative approach and the thematic interpretation method (tafsir maudh?’i), this research connects relevant Qur’anic verses with contemporary social realities. The findings reveal that weak faith, family neglect, negative environmental influences, and a lack of role models are dominant factors in the moral decline of adolescents. As a solution, the Qur’an offers a moral foundation through aqidah education, the cultivation of exemplary values (uswah hasanah), and the strengthening of self-control (muhasabah). This study highlights the importance of collaboration between families, educational institutions, and society in revitalizing Qur’anic values as both preventive and curative efforts against the moral degradation of the younger generation.